An exploration of the involvement of people with disabilities in poverty-reduction strategies in Malawi - Massah, Bonface Ophiyah (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil (Rehabilitation))-- University of Stellenbosch, 2011.